Elaboration of Tasybih in the Qur’an in Surah Al-Baqarah - Bagaskara, Syamsul Ma'arif; Sausan, Muna (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2024)
The passage of human knowledge that is increasing will be science. One area of such knowledge is related to the Quran, which consists of pronunciation and meaning. The purpose of this writing is to deepen and examine more about the Tasybih section of Bayan knowledge, which is the root of the Balaghah science itself. This research method uses descriptive and analytical studies, and the preparation of this work uses a type of library research, aiming to conceptualize various aspects related to Tasybih in Surat Al-Baqarah. Thus, this research aims to be more analytical, investigative, factual, logical, and accurate. The consequence of the findings in this study is regarding the variations of Tasybih in Surat Al-Baqarah. This Surat is categorized as a Madaniyyah Surat, meaning it was revealed in Madinah. With a total of 286 verses, it uses a beautiful style of language and very charming parables. Therefore, this research is essential to understand correctly the rules of Balaghah science, one of which is Tasybih. Surat Al-Baqarah is particularly notable for its intricate use of language and rhetorical devices, making it a prime subject for studying Tasybih a figure of speech involving comparisons, often used to create vivid imagery and deeper meaning in the text. By delving into the various instances and forms of Tasybih in Surat Al-Baqarah, this research sheds light on how these rhetorical techniques enhance the expressive power and aesthetic appeal of the Quranic message. In addition, this study also explores the broader implications of Tasybih in the context of Islamic teachings and its role in conveying complex theological and moral concepts in an accessible and impactful manner. Understanding these literary devices is crucial for appreciating the depth and nuance of the Quran's message and for developing a more profound connection with the text. By meticulously analyzing the use of Tasybih in Surat Al-Baqarah, this research contributes to a deeper appreciation of the Quran's linguistic artistry and the sophisticated ways in which it communicates its divine message. This study not only highlights the significance of Balaghah in Islamic scholarship but also underscores the importance of literary and rhetorical analysis in the study of religious texts.